Clinical performance of 6% hydrogen peroxide containing TiO2N nanoparticles activated by LED in varying wavelengths—a randomized clinical trial - Trevisan, Tamara Carolina [UNESP]; Bortolatto, Janaina Freitas [UNESP]; Rizzi, Giovana [UNESP]; Meloto, Bruna Tavoni [UNESP]; Dantas, Andrea Abi Rached [UNESP]; de Oliveira Junior, Osmir Batista [UNESP] (Springer Nature, 2022)
This randomized, controlled, and double-blinded clinical trial evaluated the clinical performance of dental bleaching performed with 6% hydrogen peroxide containing TiO2–N nanoparticles exposed to blue and violet activation lights. Forty volunteers, selected according to the inclusion and exclusion criteria, were randomly distributed into four experimental groups (n = 10): 35% hydrogen peroxide (PH35)—control; 6% hydrogen peroxide (PH6) containing TiO2–N nanoparticles without light activation; PH6 activated with a blue LED (PH6A); and PH6 activated with a violet LED (PH6V). The three bleaching sessions consisted of 3 consecutive 16-min applications of the bleaching agent described for each group. The groups receiving LED activation were exposed to light intermittently every 1 min, with a total exposure time of 8 min in each application. Efficacy was determined by the color variation in the upper central incisors and canines, using reflectance spectroscopy analysis performed by a calibrated evaluator (ICC = 0.83). Tooth sensitivity was characterized according to the presence and intensity (SI) self-recorded in specific forms. The group treated with PH6V was as effective as the control group (PH35), whereas the groups PH6A and PH6 showed lower efficacy. Regardless of the activation, all groups treated with 6% hydrogen peroxide were less likely to cause sensitivity compared to the control group (PH35). The use pf PH6 activated by LED violet resulted in an effective and safe clinical protocol for in-office dental bleaching. Trial registration number: RBR-8pbydg; registration date: 08/29/2017.
Keywords: Efficacy; Hydrogen peroxide; Nanotechnology; Titanium dioxide; Tooth bleaching; Tooth sensitivity